Dentinogenic ghost cell tumor: A case report (Journal of Pathology of Nepal, 2019)
Dentinogenic ghost cell tumor is a rare odontogenic neoplasm that was initially considered to be a solid variant of Calcifying Odontogenic Cyst with locally aggressive behavior. Dentinogenic ghost cell tumor comprises less than 0.5% of all odontogenic tumors and characterized histologically by an ameloblastomatous epithelium with an area of ghost cell formation and a varying amount of dentinoid. Herein we report a case of intraosseous Dentinogenic ghost cell tumor in a 32 years old male patient with a clinical presentation of bony hard swelling in the left mandibular region. The diagnosis was made on the basis of histopathological findings and histochemical analysis.